2021
DOI: 10.1038/s41390-021-01649-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between neurofilament light-chain protein, brain structure, and chronic kidney disease

Abstract: Background: Neurofilament light chain (NfL) protein is a blood-based marker of neuroaxonal injury. We sought to 1) compare plasma NfL levels in children with chronic kidney disease (CKD) and healthy peers, 2) characterize the relationship between NfL level and kidney function, and 3) evaluate NfL as a predictor of abnormal brain structure in CKD. Methods: Sixteen children with CKD due to congenital kidney anomalies and 23 typically developing peers were included. Plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…It may be difficult to investigate the dynamics of CSF and serum NfPs in chronic neurodegenerative diseases such as AD and PD without treatments that can cure them. Because it is suggested that serum NfL fragments may be cleared by the kidneys, renal function ought to be considered when interpreting serum NfL levels (Korley et al, 2019;Van Der Plas et al, 2021).…”
Section: Dynamics Of Extracellular Neurofilament Proteins and Fragmentsmentioning
confidence: 99%
“…It may be difficult to investigate the dynamics of CSF and serum NfPs in chronic neurodegenerative diseases such as AD and PD without treatments that can cure them. Because it is suggested that serum NfL fragments may be cleared by the kidneys, renal function ought to be considered when interpreting serum NfL levels (Korley et al, 2019;Van Der Plas et al, 2021).…”
Section: Dynamics Of Extracellular Neurofilament Proteins and Fragmentsmentioning
confidence: 99%
“…Third, cutoff of NfL in blood might vary depending on the disease severity and quantification techniques. It should also be noted that blood NfL is relatively low specificity and also abnormal in other conditions including nervous system diseases and renal disease (Gaetani et al, 2019;van der Plas et al, 2021). While these methods are promising, future studies are needed to substantiate their usefulness as biomarker in early parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that between-group factors other than central axonal injury such as peripheral nerve damage, impaired renal function and/or vascular neuropathy may be responsible for elevated plasma NfL levels in individuals with Wolfram syndrome ( Bischof et al, 2018 ; Khalil et al, 2018 ; Sandelius et al, 2018 ; Akamine et al, 2020 ; Frempong et al, 2021 ). Future studies using CSF NfL samples and MR diffusion studies of tissue microstructural integrity, known to be impaired in Wolfram syndrome ( Lugar et al, 2016 ), will help to determine whether the elevated NfL is primarily due to central axonal injury or other aspects of Wolfram syndrome (e.g., diabetes, ER dysfunction) ( Piehl et al, 2018 ; Akamine et al, 2020 ; van der Plas et al, 2021 ). Unfortunately, the current study was not powered to detect relationships between diffusion MRI-based tissue microstructural integrity and NfL levels since these measures were not always obtained during the same clinic year in individuals with Wolfram syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofilament light chain levels fluctuate non-linearly over the lifespan in healthy individuals and, in normal aging, elevated NfL levels cross-sectionally and longitudinally relate to brain volume loss presumably due to increasing levels of neuroaxonal injury ( Bridel et al, 2019 ; Khalil et al, 2020 ; Ashton et al, 2021 ). Risk for or presence of disease often alters the relationship between age and NfL levels ( Bridel et al, 2019 ; Khalil et al, 2020 ; Ashton et al, 2021 ; van der Plas et al, 2021 ). The subset of siblings in our control group, composed of children and adolescents, had plasma NfL levels similar to those of the control parents in our study and to serum NfL levels in similarly aged healthy controls in a pediatric MS study ( Reinert et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation